Cross‐sectional study about impact of parental smoking on rhinitis symptoms in children. (4th April 2017) - Faraldo‐García, A.; Lopez‐Silvarrey, A.; Pertega, S.; Cruz, M.‐J.; Sampedro, M.; Sánchez‐Lastres, J.; San‐José Gónzalez, M.A.; Bamonde, L.; Garnelo, L.; Pérez‐Castro, T.; Valdés‐Cuadrado, L.; Gonzalez‐Barcala, F.‐J.
Abstract: Objective: Assess the prevalence of rhinitis and exposure to environmental tobacco smoke (ETS) of children in our community and its relationship with symptoms of rhinitis Methods (design, setting, participants, main outcome measures): Cross‐sectional study using questionnaire on rhinitis of the International Study of Asthma and Allergies in Childhood, in children (6‐7 years) and adolescents (13‐14 years). Categories: "rhinitis ever", "recent rhinitis", "recent rhinoconjunctivitis", "severe rhinoconjunctivitis". Parental smoking: (i) neither parent smokes; (ii) only the mother smokes; (iii) only the father smokes; and (iv) both parents smoke. Odds ratio of the prevalence of symptoms of rhinitis according to ETS exposure was calculated using logistic regression. Results: 10 690 children and 10 730 adolescents. The prevalence of "rhinitis ever" in children: 29.4%, "recent rhinitis" 24%, "recent rhinoconjunctivitis" 11.5% and "severe rhinoconjunctivitis" 0.1%. In adolescents: 46.2%, 34.5%, 16.2% and 0.2%, respectively. Environmental tobacco smoke exposure in the home occurred in 51% of cases. Parental smoking was associated with a higher prevalence of forms of rhinitis in adolescents when only the mother was a smoker. In children when both parents were smokers. Conclusion: Rhinitis is highly prevalent in our community. Environmental tobacco smoke exposure is still very common. The relationship between ETS and rhinitis symptoms in children of this community is not as robust as that found for asthma.